2015
DOI: 10.1002/btpr.2150
|View full text |Cite
|
Sign up to set email alerts
|

Trace levels of the CHO host cell protease cathepsin D caused particle formation in a monoclonal antibody product

Abstract: Chinese hamster ovary (CHO) cells are often used to produce therapeutic monoclonal antibodies (mAbs). CHO cells express many host cell proteins (HCPs) required for their growth. Interactions of HCPs with mAbs can sometimes result in co-purification of trace levels of 'hitchhiker' HCPs during the manufacturing process. Purified mAb-1 product produced in early stages of process optimization had high HCP levels. In addition, these lots formed delayed-onset particles containing mAb-1 and its heavy chain C-terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 31 publications
1
84
0
Order By: Relevance
“…Cathepsins in the culture supernatants have been reported as enzymes that break down proteins23242526. In particular, Ctsd cleaves mAbs, generating C-terminal heavy chain fragments12. In this study, five different cathepsins (Ctsa, Ctsb, Ctsd, Ctsl, and Ctsz) were identified, with their concentrations gradually increasing during the cultures (see Supplementary Table S7).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Cathepsins in the culture supernatants have been reported as enzymes that break down proteins23242526. In particular, Ctsd cleaves mAbs, generating C-terminal heavy chain fragments12. In this study, five different cathepsins (Ctsa, Ctsb, Ctsd, Ctsl, and Ctsz) were identified, with their concentrations gradually increasing during the cultures (see Supplementary Table S7).…”
Section: Discussionmentioning
confidence: 73%
“…These HCPs were themselves classified into various clusters. For example, cathepsin D (Ctsd) generates C-terminal heavy chain fragments by cleaving mAbs12. Ctsd and other cathepsin proteases including Ctsa, Ctsb, Ctsl, and Ctsz were associated with lysosome and classified in cluster 2 for both batch and fed-batch cultures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang, Hunter, & Mozier, 2009), there may still be specific HCPs in the final product that can cause degradation of the drug product or elicit an immune response in patients (Bee et al, 2015;Fischer et al, 2017;Gao et al, 2011;Lim et al, 2017;Robert et al, 2009). Proteomic studies have shown that certain HCPs such as phospholipase B, lipoprotein lipase, and some serine proteases can persist at detectable levels through multiple chromatographic processes (Bee et al, 2015;B. The carry-over of HCPs through all the polishing steps to the final drug product can be attributed to either coelution with the product during chromatographic steps or product association via nonspecific interactions (Gaitatzis, Sisodiya, & Sander, 2012;Shukla & Hinckley, 2008;Yuk et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…PLBL2 was identified to interact with different mAbs and to "hitchhike" through the entire process, resulting in degradation of some of the formulation components. Cathepsin D was found to cause mAb degradation in the formulated drug product (Bee et al, 2015) and various strategies have been used to remove residual cathepsin D, either by optimal washes during protein A capture or by thermal inactivation of the protease (Lim et al, 2017). Cathepsin D was found to cause mAb degradation in the formulated drug product (Bee et al, 2015) and various strategies have been used to remove residual cathepsin D, either by optimal washes during protein A capture or by thermal inactivation of the protease (Lim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%